TOWEL CURL EXERCISE BERPENGARUH TERHADAP PENINGKATAN KESEIMBANGAN STATIS ANAK DENGAN FLAT FOOT - Rindu Febriyeni Utami Febri Yolanda Syafri (Universitas Fort de Kock Bukittinggi, 2021)
ABSTRACTThe growth and development of children is determined by innate and environmental factors. One of the problems encountered is Flat foot. Flat foot is no visible arch in the foot or flat feet. Flat foot will affect balance. One of the physiotherapy can be used is Towel curl exercise. The study aimed to determine The Effect of Towel Curl Exercise to Increase Static Balance of Children with Flat Foot at 7-9 Years at Public Elementary School (SD Negeri 10 Sampiran), Aur Birugo Tigo Baleh District in 2021. The type of this study was quasi-experimental with a one group pretest-posttest design. The population was students at 7-9 years old, there were 133 people. By using accident sampling technique with the inclusion and exclusion criteria, 10 respondents were chosen as the samples. It was analyzed by univariate and bivariate analysis.The results showed that the average respondent's static balance before the intervention was 2.45 seconds (less). The average respondent's static balance after the intervention was 4.16 seconds (enough), it means that the towel curl exercise had a significant effect on static balance in children with flat feet, there was an increase in the average balance score after 12 interventions with an average difference of 1.707 seconds and p value = 0.000. It was concluded that the Towel Curl Exercise to Improve the Static Balance of Children with Flat Foot at 7-9 Years old at SD Negeri 10 Sapiran, Aur Birugo Tigo Baleh District in 2021, It could be done at home with the help of parents and prevent children from experiencing Flat Foot at an early age.Keywords : Flat Foot, Static Balance and Towel Curl ExerciseABSTRAKPertumbuhan dan perkembangan anak ditentukan oleh faktor bawaan dan lingkungan. Salah satu permasalahan yang di temui yaitu Flat foot. Flat foot adalah tidak adanya lengkung kaki atau kaki datar. Flat foot akan berpengaruh kepada keseimbangan. Salah satu tindakan fisioterapi yang dapat digunakan yaitu Towel curl exercise. Penelitian ini bertujuan untuk mengetahui Pengaruh Towel Curl Exercise Terhadap Peningkatan Keseimbangan Statis Anak dengan Flat Foot.Metode penelitian yang digunakan Quasi-eksperiment dengan pendekatan one group pretest-posttest design. Populasi adalah siswa umur 7-9 tahun yang berjumlah 133 orang. Sampel pada penelitian ini menggunakan teknik accident sampling dengan sampel sebanyak 10 responden yang sesuai dengan kriteria inklusi dan eksklusi. Analisis data menggunakan analisis univariate dan bivariate. Hasil penelitian menunjukkan rerata keseimbangan statis responden sebelum intervensi adalah 2,45 detik (kurang). Rerata keseimbangan statis responden sesudah intervensi adalah 4,16 detik (cukup) sehingga pemberian towel curl exercise berpengaruh signifikan terhadap keseimbangan statis pada anak dengan flat foot, dimana terjadi peningkatan rerata skor keseimbangan setelah 12 kali intervensi dengan beda rerata 1,707 detik dan nilai p = 0,000. Disimpulkan bahwa Towel Curl Exercise Terhadap Peningkatan Keseimbangan Statis Anak dengan Flat Foot Usia 7-9 Tahun di SD Negeri 10 Sapiran Kecamatan Aur Birugo Tigo Baleh Tahun 2021 ini bisa dilakukan di rumah dengan bantuan orang tua dan mencegah anak yang mengalami Flat Foot di usia dini.Kata Kunci : Flat Foot, Keseimbangan Statis dan Towel Curl Exercise